Microbial Dysbiosis in Common Variable Immune Deficiencies: Evidence, Causes, and Consequences. Issue 3 (March 2017) - Berbers, Roos-Marijn; Nierkens, Stefan; van Laar, Jacob M.; Bogaert, Debby; Leavis, Helen L.
Abstract : Common variable immunodeficiency (CVID) is an immune disorder that not only causes increased susceptibility to infection, but also to inflammatory complications such as autoimmunity, lymphoid proliferation, malignancy, and granulomatous disease. Recent findings implicate the microbiome as a driver of this systemic immune dysregulation. Here, we critically review the current evidence for a role of the microbiome in the pathogenesis of CVID immune dysregulation, and describe the possible immunologic mechanisms behind causes and consequences of microbial dysbiosis in CVID. We integrate this evidence into a model describing a role for the gut microbiota in the maintenance of inflammation and immune dysregulation in CVID, and suggest research strategies to contribute to the development of new diagnostic tools and therapeutic targets. Trends: The etiology of CVID and associated immune dysregulation remains incompletely understood but several lines of evidence now suggest a role for increased levels of microbial translocation. Microbial translocation in CVID is linked to systemic inflammation and cell exhaustion, and this process may persist even under immunoglobulin substitution therapy. Systemic inflammation and cell exhaustion are associated with immune dysregulation symptoms in CVID, such as autoimmunity, lymphoproliferation, malignancy, and granulomatous disease. CVID patients with immune dysregulation have reduced microbial diversity in their gut compared to CVID patients without immune dysregulation and healthy controls.